Medical imaging systems : an introductory guide - Maier, Andreas (Andreas K.); Steidl, Stefan; Christlein, Vincent; Hornegger, Joachim (Cham, Switzerland : Springer Open, 2018)
This open access book gives a complete and comprehensive introduction to the fields of medical imaging systems, as designed for a broad range of applications. The authors of the book first explain the foundations of system theory and image processing, before highlighting several modalities in a dedicated chapter. The initial focus is on modalities that are closely related to traditional camera systems such as endoscopy and microscopy. This is followed by more complex image formation processes: magnetic resonance imaging, X-ray projection imaging, computed tomography, X-ray phase-contrast imaging, nuclear imaging, ultrasound, and optical coherence tomography.
Introduction -- System Theory -- Image Processing -- Endoscopy -- Microscopy -- Magnetic Resonance Imaging -- X-ray Imaging -- Computed Tomography -- X-ray Phase Contrast: Research on a Future Imaging Modality -- Emission Tomography -- Ultrasound -- Optical Coherence Tomography -- Acronyms.
Includes bibliographical references and indexes.
Description based on online resource; title from PDF title page (viewed February 14, 2020).
Keywords: Diagnostic imaging; Diagnostic Imaging; Imagerie pour le diagnostic; Diagnostic imaging